Fatigue resonant tests on S140 and S150 grade corroded drill pipe connections and pipe bodies. (July 2020) - Santus, C.; Burchianti, A.; Inoue, T.; Ishiguro, H.
Abstract: A resonant test rig aimed at fatigue tests on tubular elements is presented in this paper, showing the working principle and control strategy. Corroded drill pipe connections and pipe bodies with different sizes and different steel grades were tested. A relatively high stress amplitude was applied to all the specimens. The fatigue initiation was observed in the central region of the pipe specimens, where the stress amplitude is highest, and away from the tool joints of the connection specimens, mainly because of the different outer diameters. The fatigue crack was initiated at the pitting corrosion sites, which limited the potential fatigue strength of the drill pipes. Small-scale tests were also performed, showing a much higher base material strength. A comparison analysis was thus used to evaluate the fatigue size and surface condition effects, and to estimate the maximum fatigue stress concentration factors at the connections. Graphical abstract: Image 1 Highlights: Resonant fatigue test bench, working principle and specimen setup definitions. S140 and S150 steel grade drill pipes were tested, both Connection and pipe body. SEM observation showed the corrosion damage causing fatigue initiation sites. Small scale fatigue test results higher than full scale tests by a factor 2.5. Assessment of the connection maximum fatigue stress concentration factors.